A cosmological model with compact space sections and low mass density - Fagundes, Helio V. (Springer Nature, 1982)
A general relativistic cosmological model is presented which has closed space sections and mass density below a critical density similar to that of Friedmann's models. The model may predict double images of cosmic sources: a hint is made at a qualitative application to quasar astronomy. © 1982 D. Reidel Publishing Company.